Manufacturing Productivity: Effects of Service Sector Innovations and Institutions - Neil Foster-McGregor; Johannes Pöschl; Robert Stehrer (The Vienna Institute for International Economic Studies (wiiw), 2012)
A major international transmission channel of productivity increases is trade in intermediate products and services. This paper analyses international rent spillovers at the industry level and for the first time investigates effects from the service sector in this international framework. The World Input-Output Database (WIOD) allows us to improve over the traditional approach of using trade in intermediates in the estimation of international spillovers by making use of input-output linkages between industries in different countries. Our results using this novel approach confirm the productivity effects from international manufacturing spillovers found in recent literature. As regards services, which provide a substantial component of the manufacturing sectors' inputs, our results indicate significant positive productivity effects from innovations in this sector. Furthermore, we control for the effect of domestic institutions on productivity. A high quality of contract enforcement and property rights protection is found to foster firm development and increase productivity in the country. Last but not least educational institutions in the reporter country are an important determinant of productivity developments.
Keywords: F14; F43; O31; O43; 330; productivity; research and development; services; spillovers; institutions